2020
DOI: 10.1002/ijgo.13359
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the COVID‐19 waters with chronic pelvic pain

Abstract: Despite changes in healthcare approaches due to the COVID‐19 pandemic, patients with chronic pelvic pain should be assured of optimal access to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“… 58 , 59 This concern for family safety could then potentially lead to frustration, anger, and resentment toward those ignoring COVID-19 precautions. Several studies have also identified disruption to the health care system as a direct result of the COVID-19 pandemic, specifically focusing on the impacts of triaging or prioritizing acute physical needs, 24 leading to individuals with chronic pain experiencing delayed access 60–63 and increased anxiety, helplessness, and pain. 24 These findings highlight the importance of ensuring that individuals with chronic conditions continue to have stable access to various therapies even amidst public health crises.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 58 , 59 This concern for family safety could then potentially lead to frustration, anger, and resentment toward those ignoring COVID-19 precautions. Several studies have also identified disruption to the health care system as a direct result of the COVID-19 pandemic, specifically focusing on the impacts of triaging or prioritizing acute physical needs, 24 leading to individuals with chronic pain experiencing delayed access 60–63 and increased anxiety, helplessness, and pain. 24 These findings highlight the importance of ensuring that individuals with chronic conditions continue to have stable access to various therapies even amidst public health crises.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also identified disruption to the health care system as a direct result of the COVID-19 pandemic, specifically focusing on the impacts of triaging or prioritizing acute physical needs, 24 leading to individuals with chronic pain experiencing delayed access 60–63 and increased anxiety, helplessness, and pain. 24 These findings highlight the importance of ensuring that individuals with chronic conditions continue to have stable access to various therapies even amidst public health crises. 64 Utilization of virtual telemedicine can help to improve access for some individuals, 65 , 66 but such online interventions must include evidence-based, multidisciplinary pain management supports 64 and, as highlighted in our analysis, virtual care may not always be a suitable alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As healthcare providers treating chronic pelvic pain patients (a vulnerable population), we need to adapt with them and offer all the tools available to complement their treatment [ 18 ]. Many women suffering from pelvic pain have delayed seeking treatment.…”
Section: Discussionmentioning
confidence: 99%
“…À cet effet, plusieurs expert•e•s évoquent une possible augmentation de la douleur chronique après la pandémie, que cette douleur soit due à l'hospitalisation ou aux conséquences du virus chez les gens infectés ou à l'exacerbation des facteurs de risque chez les individus (Clauw et al, 2020;Elran-Barak & Mozeikov, 2020). Certain•e•s auteur•trice•s ont aussi mis en lumière que la réduction des soins pour les personnes vivant avec de la douleur chronique durant la pandémie en raison du délestage pourrait mener à l'augmentation de la douleur, de l'anxiété et du stress (Clauw et al, 2020;Pope, 2020;Villegas-Echeverri & Carrillo, 2020). D'autre part, une étude de Pagé et al (2021) rapporte que 69% des individus vivant avec de la douleur chronique ont noté une détérioration de leur condition durant la première vague de la pandémie.…”
Section: Douleur Chronique Et Détresse Psychologique En Contexte De C...unclassified